An empirical model for estimating the atmospheric transmittance of upward infrared radiation at different altitudes. Issue 11 (1st December 2016) - Dai, Qiumin; Fang, Xiande; Zhao, Yingjie; Xing, Daoming
Abstract: The upward infrared (IR) radiation is one of the most important factors that affect the thermal characteristics of light-than-air (LTA) vehicles. Therefore, it is necessary to propose an accurate model to evaluate the upward atmospheric transmittance. The upward IR atmospheric transmittances of 6 different atmospheric models at the altitude from sea level to 30 km are obtained from the MODTRAN atmospheric radiative transfer code. Based on the data, a new upward IR atmospheric transmittance correlation related to pressure and vertical water column is proposed by regression analysis. It has excellent prediction accuracy with the coefficient of determination of 0.928, the root mean square error of 0.028, and the mean absolute percentage error of 2.68% for the database. Based on the new correlation, the thermal characteristics of a stratospheric airship located in tropics in midsummer are numerical studied and discussed.